2020
DOI: 10.3389/fmicb.2020.00058
|View full text |Cite
|
Sign up to set email alerts
|

Enrichment of Anaerobic Syngas-Converting Communities and Isolation of a Novel Carboxydotrophic Acetobacterium wieringae Strain JM

Abstract: Syngas is a substrate for the anaerobic bioproduction of fuels and valuable chemicals. In this study, anaerobic sludge was used for microbial enrichments with synthetic syngas and acetate as main substrates. The objectives of this study were to identify microbial networks (in enrichment cultures) for the conversion of syngas to added-value products, and to isolate robust, non-fastidious carboxydotrophs. Enrichment cultures produced methane and propionate, this last one an unusual product from syngas fermentati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
44
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 29 publications
(45 citation statements)
references
References 45 publications
1
44
0
Order By: Relevance
“…on May 30, 2021 by guest http://aem.asm.org/ Downloaded from Previously, we described an enrichment culture that produced acetate and propionate from CO (15). This culture was predominantly composed of microorganisms affiliated with Acetobacterium wieringae (87 % relative abundance), and propionigenic bacteria closely related to Pelobacter propionicus and Anaerotignum neopropionicum (1 and 2 %, respectively) (15).…”
Section: Introductionmentioning
confidence: 98%
See 2 more Smart Citations
“…on May 30, 2021 by guest http://aem.asm.org/ Downloaded from Previously, we described an enrichment culture that produced acetate and propionate from CO (15). This culture was predominantly composed of microorganisms affiliated with Acetobacterium wieringae (87 % relative abundance), and propionigenic bacteria closely related to Pelobacter propionicus and Anaerotignum neopropionicum (1 and 2 %, respectively) (15).…”
Section: Introductionmentioning
confidence: 98%
“…Ac. wieringae strain JM was subsequently isolated from this enrichment (15). When grown solely on CO, strain JM produced acetate and ethanol, but not propionate.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Acetobacterium woodii encodes only a single Rnf complex (21), but Acetobacterium wieringae and Acetobacterium sp. MES1 were found to encode two (14,63,64). The function of the second Rnf complex in Acetobacterium is unknown, but closer examination of the remaining Acetobacterium genomes revealed that the majority of Acetobacterium genomes encode a second rnfCDGEAB cluster (Data Set S2).…”
Section: Resultsmentioning
confidence: 99%
“…UBA6819 were the only strains to encode a complete AdhE with 87% sequence identity to A. woodii (Data Set S2). Despite the lack of AdhE in the other species of Acetobacterium, species like A. wieringae are capable of growth on ethanol (Table 3) (64,71,(75)(76)(77). It is likely that A. wieringae and the other Acetobacterium strains that do not encode the A. woodii-type bifunctional acetaldehyde-CoA/alcohol dehydrogenase employ an alternative pathway for ethanol oxidation.…”
Section: Resultsmentioning
confidence: 99%